2015
DOI: 10.1038/jhh.2015.61
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in persons with apparent treatment-resistant hypertension on at least four antihypertensives

Abstract: Little is known about the impact of treatment-resistant hypertension (TRH) on health-related quality of life (HrQoL). We aimed to compare HrQoL measures in adults with apparent TRH (aTRH) and non-resistant hypertension among nationally representative US Medical Expenditure Panel Survey data pooled from 2000 to 2011. Cohorts compared were adults with aTRH (⩾2 unique fills from ⩾4 antihypertensive classes during a year) versus non-resistant hypertension (those with hypertension not meeting the aTRH definition). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 37 publications
0
16
0
1
Order By: Relevance
“…Mounting evidence demonstrates that resistant hypertension––defined even as simply as requiring four or more antihypertensive drugs to achieve office blood pressure (BP) control––is associated with impaired health‐related quality of life and a substantially greater risk of adverse cardiovascular outcomes and death relative to nonresistant hypertension . This evidence is concerning given that an estimated one in five treated hypertensive patients in the United States meets this definition of resistant hypertension and, of these, most have uncontrolled BP .…”
mentioning
confidence: 99%
“…Mounting evidence demonstrates that resistant hypertension––defined even as simply as requiring four or more antihypertensive drugs to achieve office blood pressure (BP) control––is associated with impaired health‐related quality of life and a substantially greater risk of adverse cardiovascular outcomes and death relative to nonresistant hypertension . This evidence is concerning given that an estimated one in five treated hypertensive patients in the United States meets this definition of resistant hypertension and, of these, most have uncontrolled BP .…”
mentioning
confidence: 99%
“…6 Emerging evidence suggests that RH is associated with increased risk for major adverse cardiovascular (CV) events and mortality and worse health-related quality of life, compared with nonresistant hypertension (non-RH). [9][10][11][12][13][14][15][16] Consequently, RH has been identified as a priority research area. 7,17 Multiple lines of empiric evidence suggest that women are at greater risk of developing RH than men: mean BP is demonstrably higher in postmenopausal women than agematched men 18 ; women are more likely than men to be treated with antihypertensive drugs, but less likely to achieve BP control 1,6,[19][20][21][22] ; and female sex has been repeatedly identified as an independent predictor of RH.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Moreover, the prevalence of TRH seems to be increasing in the United States, highlighting the importance in addressing this rising health care problem. 6,7 Previous studies have shown that TRH is associated with worse health-related quality of life 8 and increased risk of cardiovascular outcomes and mortality relative to nonresistant hypertension. 3,5,9,10 In 2008, the American Heart Association (AHA) published a scientific statement identifying specific management strategies for patients with TRH, including promoting use of long-acting thiazide diuretics (eg, chlorthalidone and indapamide), addition of aldosterone receptor antagonists to the existing regimens, and withdrawal of potentially interfering medications (eg, nonsteroidal anti-inflammatory drugs) 11 ; these recommendations have been largely echoed elsewhere.…”
mentioning
confidence: 99%